Foreword Chairman 1 ICUDBE 2015 - Abdul Rahim, Asiah (2015)
I would like to express my appreciation to all of our guests, presenter and participants for sparing some time despite of the busy schedule to be part of this meaningful event. As the chairman of ICUDBE2015, I would like to thank you IIUM, Department Standards Malaysia and Putrajaya Corporation in giving the trust to Kaed Universal Design Unit (KUDU) to organise such a big conference for the fourth time. . KAED Universal Design Unit (KUDU) of IIUM was formed in 2008 with the intention to promote the application of universal design in the built environment and product design, as well as to disseminate research findings through international conferences, symposiums, workshops and product competitions.